(untitled) (Journal of the College of Education for Women, 2019)
This study has been developed axes of the search, including: Search (deliberative) language and idiomatically, and Description Language (b social phenomenon), and the definition of the theory of (acts of speech), and discussed the problem of the conflict between tradition and innovation, as defined objectively have a target aimed at reviving the deliberative thought when Arab scholars , and the balance between the actual done Arab and Western rhetoric, but Meet in intellectual necessity, a sober reading that preserve the Arab language prestige, and its position in the light of the growing tongue Sciences, as long as we have inherited minds unique, and heritage huge able to consolidate the Arab theory lingual in linguistics.